2017
DOI: 10.1002/14651858.cd011425.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Computer and mobile technology interventions for self-management in chronic obstructive pulmonary disease

Abstract: Although our review suggests that interventions aimed at facilitating, supporting, and sustaining self-managment in people with COPD and delivered via smart technology significantly improved HRQoL and levels of activity up to six months compared with interventions given through face-to-face/digital and/or written support, no firm conclusions can be drawn. This improvement may not be sustained over a long duration. The only included study that measured outcomes up to 12 months highlighted the need to ensure sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
165
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(189 citation statements)
references
References 44 publications
5
165
3
Order By: Relevance
“…The poor use of the many functions of telephones and mobile phones as the main intervention may be due to the fact that researchers were more likely to believe in the effectiveness of traditional interventions, such as training and consultation in person, compared to technology-based interventions. On contrary to this, a recently published systematic review showed that technology-based interventions have a greater effect on the quality of life in patients with chronic obstructive pulmonary disease compared to traditional interventions (32). In the present review, only one study that used phones as its main intervention showed improvements in weight and BMI outcomes in its inter- vention group compared to the control; it should be noted that in the methodological assessment this study was categorized as high quality (11).…”
Section: Discussionmentioning
confidence: 88%
“…The poor use of the many functions of telephones and mobile phones as the main intervention may be due to the fact that researchers were more likely to believe in the effectiveness of traditional interventions, such as training and consultation in person, compared to technology-based interventions. On contrary to this, a recently published systematic review showed that technology-based interventions have a greater effect on the quality of life in patients with chronic obstructive pulmonary disease compared to traditional interventions (32). In the present review, only one study that used phones as its main intervention showed improvements in weight and BMI outcomes in its inter- vention group compared to the control; it should be noted that in the methodological assessment this study was categorized as high quality (11).…”
Section: Discussionmentioning
confidence: 88%
“…However, caution in application of technology for learning and self‐management is needed as audits of web‐based resources available to people with COPD suggests that content and quality significantly vary on sites such as YouTube and Pinterest . Furthermore, adverse event rates were significantly higher in the smart technology groups of the aforementioned review . This may relate to the potential decreased capacity for learning of people with COPD, who are at increased risk for co‐morbidities that can impact the learning process including anxiety, depression and cognitive impairment .…”
Section: Technology‐enabled Patient Education and Self‐management Supmentioning
confidence: 99%
“…As of May 2018, a total of 22 systematic reviews examining one or more learning focused interventions for people with respiratory‐related conditions compared to usual care had been published in the Cochrane Database of Systematic Reviews . The patient population groups include adults with asthma (11 reviews), COPD (3 reviews), smoking cessation (2 reviews), cystic fibrosis (1 review), bronchiectasis (1 review), acute upper respiratory tract infections (1 review), lung cancer (1 review), obstructive sleep apnoea (1 review) and tuberculosis (1 review) . The reviews reported two main categories of educational interventions: (i) didactic‐focused teaching for knowledge and (ii) learning experiences for developing self‐management strategies.…”
Section: Impact Of Education Within Prmentioning
confidence: 99%
See 1 more Smart Citation
“…A Cochrane review of the recent literature suggested that patients with chronic lung disease who used smart devices for self-management at home maintained their level of activity and improved quality of life; however, the long-term effects were unclear, and the benefits of smart homecare were not equally given to everyone. For example, it derived greater benefit with the patients who showed high interest in using smart devices 23) . Bhattarai and Phillips 24) also suggested that digital and mobile technology could be applied to the pain management of the elderly, but the level of technology should be more advanced than the current ones, and a thorough analysis and verification of such technology demand are required.…”
Section: Clinical Evidence and Institutional Aspectsmentioning
confidence: 99%